1.) 4 - t = 3(t - 1) - 5
4 - t = 3t - 3 - 5
4 - t = 3t - 8
3t + t = 4 + 8
4t = 12
t = 12/4 = 3
2.) 8x - 2(x + 1) = 2(3x - 1)
8x - 2x - 2 = 6x - 2
6x - 2 = 6x - 2
0 = 0
solution is identity.
3.) 3(c - 2) = 2(c - 6)
3c - 6 = 2c - 12
3c - 2c = -12 + 6
c = -6
4.) 0.5(m + 4) = 3(m - 1)
0.5m + 2 = 3m - 3
3m - 0.5m = 2 + 3
2.5m = 5
m = 5/2.5 = 2
m = 2
Convert the cm to feet for the base and the height:
12/2 = 6 x 3 = 18 feet
9/2 = 4.5 x 3 = 13.5 feet
area = 1/2 x base x height
Area = 1/2 x 18 x 13.5
Area = 121.5 square feet
answer: 121.5 square feet
Answer:
3x - 4 = -12
Step-by-step explanation: